Reading Holy Qur’an to Improve Verbal Fluency in Elderly - Siti Munawaroh; Yunia Hastami; Adji Suwandono; Hartono Hartono; Ari Natalia Probandari; Fitriana Herawati; Ummu Ma’rifatul Afifah; Aldira Ayu Nastiti Nur Hanifah (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2023)
The high prevalence of dementia that impairs verbal fluency has been a global source of concern. As a result, strategies for preserving or improving verbal fluency in the elderly are required. A neuroplasticity-based reading program has been shown to improve verbal fluency. This study aims to ascertain whether reading the Holy Qur'an has an effect on an older adult's ability to communicate fluently. It is an experimental study with a quasi-experimental design with pretest-posttest control groups. This study sampled 22 elderly individuals with the following criteria: age greater than 60 years, ability to speak and read the Holy Qur'an, a Mini-Mental State Examination (MMSE) score greater than 24, absence of psychiatric disorders, absence of head trauma, and absence of neurological disease. The intervention group read the Quran for two weeks, while the control group did not. Both groups were measured for Verbal fluency at the beginning and after the intervention. There were significant differences in post-test phonemic scores between the control group (CG) and the intervention group (IG) (p=0.019). Meanwhile, there was no significant difference in semantic score in all groups (p0.852). Reading the Holy Qur’an activity intervention for two weeks affected verbal fluency in the elderly by increasing phonemic but not semantic scores.